Revealing the Third Generation Myth in Family Businesses: REVEALING THE THIRD GENERATION MYTH IN FAMILY BUSINESSES - Saraswati, Sabitha Rani (Universitas Ciputra Surabaya, 2020)
A family Business is a company or business which is run and managed by a family. Hence, the purpose of this study is to find out the truth of the Third Generation myth in family businesses. This study uses a data collection method using a semi-structured interview. This research uses source triangulation method which aims to test the credibility of the data which is carried out by checking the data that has been obtained from several sources. In this study, samples will be taken from several sources. The resource person himself will be taken from the senior generation as the owner of the family businesses and the next generation. The results of this study states that the decline of family businesses did not occur solely because of the mistakes of the third generation. Therefore, the third generation myth is not true. Keywords: family business, trust, knowledge transfer, delegation, third generation